Karakteristik Pertanian Di Indonesia: Antara Tradisi, Tantangan Struktural, Dan Peluang Transformasi - Erika Wulandari; Erlin Kurniati (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
Indonesian agriculture has distinctive characteristics, namely being tradition-based, labor-intensive, and fragmented into small-scale operations. Most farmers still rely on conventional farming methods passed down through generations. Despite its abundant natural resources, Indonesia's agricultural sector continues to face various structural challenges, such as limited land ownership, low access to technology, inadequate agricultural infrastructure, and a strong dependency on weather conditions. Furthermore, agricultural modernization is often hindered by the low education level of farmers and the lack of sustainable institutional support. Nevertheless, the era of digitalization and the shift in national food policy orientation present significant opportunities for transformation in this sector. The application of smart farming technologies, mechanization, and the development of digital-based agribusiness ecosystems are potential solutions to improve productivity and farmer welfare. The transformation of Indonesian agriculture requires not only technological innovation but also a change in mindset, collaboration among stakeholders, and public policies that favor small-scale farmers. This study aims to provide a comprehensive overview of the fundamental characteristics of Indonesian agriculture, identify the structural barriers it faces, and explore opportunities for transformation toward a sustainable, inclusive, and highly competitive agricultural system. Addressing human resource development, strengthening farmer institutions, and ensuring access to financing and markets are also critical to achieving long-term agricultural resilience and food security